Nitrite‐shunt and biological phosphorus removal at low dissolved oxygen in a full‐scale high‐rate system at warm temperatures. (8th March 2020) - Jimenez, Jose; Wise, George; Regmi, Pusker; Burger, Gillian; Conidi, Daniela; Du, Weiwei; Dold, Peter
Abstract: This study presents results from the City of St. Petersburg's (Florida) Southwest Water Reclamation Facility. This high‐rate BNR plant (SRT ~ 5 days; HRT < 8 hr) achieves combined bioP and shortcut simultaneous nitrification and denitrification (SND) via nitrite in a simple BNR configuration—an anaerobic–aerobic (A/O) process without mixed liquor recycle and a 25% unaerated fraction. N removal to low effluent and nitrate and nitrite ( NO 3 -  +  NO 2 - ) concentrations occurs mainly via SND by operating the aerated zone at low DO, but still achieving near‐complete ammonium ( NH 4 + ) removal. Despite the low DO operation, very good bioP performance is achieved. Full‐scale performance data and detailed bench‐scale testing were conducted to assess the nitrogen and phosphorus removal at low DO conditions. Full‐scale results showed that the plant achieves effluent total inorganic nitrogen (TIN) and total phosphorus (TP) concentrations of approximately 2.0 mgN/L and 0.5 mgP/L, respectively, at an average influent C:N ratio of 7:1 mgCOD:mgN. Practitioner points: Simple anaerobic–aerobic (A/O) process demonstrated combined N and P removal Ammonia oxidation was not hampered by low DO (<0.5 mg/L) operation Low DO (<0.5 mg/L) operation sustained SND via nitrite pathway in a high‐rate process (HRT < 6 hr) P uptake was demonstrated at low DO which counters to the widely held understanding that high DO (>1.5 mg/L) is necessary Heterotrophic consumption of nitrite at low DO was the key to the out‐selection of nitrite‐oxidizing bacteria Abstract : Good N and P removal performance is acgieved at low DO conditions. Low DO conditions did not affect the nitrification or phosphorus uptakes rates. Low DO operation sustained SND via nitrite pathway. Heterotrophic consumption of nitrite at low DO was the key to the otu‐selection of nitrite‐oxidizing bacteria.